The Traditional Dietary Practices Followed by Gaddi Tribe of Himachal Pradesh To Manage Major discomforts and Complications Associated with Pregnancy - Bindia Dutt (International Journal of Social Sciences Review, 2023)
Pregnancy is such a condition which poses great stress in the physiology of a women leading to various complications and discomforts. This is such a stage where medicines need to be avoided as far as possible. Hence traditional practices play a major role especially in the case of tribal people as they live in far away and remote places where reaching to medical care requires time . This study was conducted on Gaddi tribe of Bhawarana block in Kangra District of Himachal Pradesh. The objective of the study was to document the traditional dietary practices followed  to manage discomforts and complications faced by pregnant women. For this study, 100 tribal women of 40 years and above from  four villages were interviewed with the belief that these women would have vast experience and knowledge of the ancient traditions as compared to those who delivered babies recently (Past 1 or 2 years). The documented practices were further validated scientifically by the experts from the fields of  Nutrition, Gynecology and Ayurveda on three point continuum as scientific, unscientific and uncertain. The information from experts were collected using questionnaire technique. The traditional practices were also validated through  Ayurvedic documents. The dietary practices followed to manage discomforts and complications during pregnancy among tribal people were followed   based on the hot and cold nature of foods